Pengaruh Ideologi Gerakan Konservasi Global di Indonesia dari Abad ke-19 hingga ke-21 - Khairina, Mustika Indah; Rahmania, Farhani Nurshafa (Universitas Gadjah Mada, 2023)
The history of the environmental conservation movement in Indonesia is not detached from the global elitist influence. The policy products of the elites’ thought and European colonialism backward originated from a few influential persons in the Western countries that came across to the Dutch East Indies through international persuades. Natural conservation that had originally been a part of indigenous daily life has been slowly transformed as a modern scientific area of works that need a specific expertise. So therefore, this research was aimed to explore and question the impact of the international conservation movement toward Indonesia for about the 19th to 20th century. The research used literature study and interview methods. Then, the analysis was focused on the aspects of Indonesia conservation policy, funding, and people’s participation.